Antimicrobial efficacy of Lactobacillus plantarum strain against the B. cereus, B. subtilis, S. aureus and E.coli strains (Bioscience Journal, 2023)
The current study aimed to detect the antimicrobial effect of cell free supernatant (CFS) of Lactobacillus plantarum strain against Gram +ve and Gram –ve bacterial strains. The strain of Lactobacillus plantarum was isolated using selective media MRS agar. The strain was characterized on the basis of the gram staining, colony morphology, the biochemical tests and the DNA sequencing based method of 16S ribotyping. A total of four test strains (The three already isolated and reported strains (E.coli, S. aureus and B. subtilis) and the one recently identified  novel strain (B. cereus) were used for the analysis of antagonistic activity of bacteriocin produced by L. plantarum strain. The CFS of L. plantarum showed zone of inhibition against all the test strains (Gram +ve and Gram –ve bacteria). The conditions favoring the growth of bacteria were associated with the antimicrobial efficacy of CFS. Bacteriocin activity of CFS remained effective after exposure to temperature stress.  Wide range of antagonistic potential of CFS of L. plantarum provides an alternative for antibiotics in pharmaceutical industry. Heat resistant feature of bacteriocin suggests its application in food industry.